PURCHASE DOCUMENTATION RE-ORGANIZING AND MANAGING IN GLOBAL SOURCING: Case study in global heavy industry company - Saarijärvi, Erkko (My University, 2016)
This research aims to find out re-organization possibilities for the case company’s purchasing documentation so that the level of purchasing requirements could be decreased and standardized. Based on supplier feedback some incoherence and the necessity of certain requirements were noticed and questioned. Furthermore, the case company has discovered that the confusion about the owner of the purchasing documentation has internally caused big variance between the documentations by different offices. Previous researches present that optimization of the requirement level as well as the development of purchase documentation has led to remarkable savings. The primary and qualitative research data was collected mainly from the internal and external stakeholders by gathering development ideas as well as information about the existing level of requirements. This case study was made using three different kinds of products, which were chosen by analysing the example project’s total costs through the Pareto-analysis. This enabled maximal benefit to the case company from both financial and duplicating point of view. This research will find out the crucial requirements of the existing purchasing documentation and create it clear hierarchy for it. Research results show that the current documentation level is far too wide and unclear. By simplifying and analysing the purchasing material in cooperation with the suppliers, the savings have been around 5%". Moreover, this scrutiny towards the material has produced a clear hierarchy as well as clarified the ownership of the documentation for the first time. This will prevent conflicts and cross revising in the future. Finally, a document model, which can be applied for all other purchasing categories, was created. This model will work as a base for a developing project in which all other product categories will be brought under similar critical estimation.
Keywords: Purchasing process; purchasing documentation; supply chain; quality requirements; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|